Mixed N-aryl/alkyl substitution favours an unusual tautomer of near-infrared absorbing azacalixphyrins. (14th October 2020) - Lavaud, Lucien; Azarias, Cloé; Canard, Gabriel; Pascal, Simon; Jacquemin, Denis; Siri, Olivier
Abstract : This work depicts the synthesis of a new azacalixphyrin presenting both aryl and alkyl substituents. The joint experimental and theoretical study supports that the substitution pattern favour an unusual 5–7 tautomer. Abstract : Azacalixphyrins are bis-zwitterionic aromatic macrocycles that feature absorption properties in the near-infrared range. Their N -substitution is an efficient strategy for tuning the absorption maxima by stabilizing different tautomeric forms depending on the nature of the substituent (alkyl or aryl give 1–5 or 2–6 tautomers, respectively). This work depicts the synthesis of a new azacalixphyrin presenting both aryl and alkyl substituents. The joint experimental and theoretical study supports that the substitution pattern can be manipulated to counterbalance the repulsion of the two peripheral cationic charges to favour an unusual 5–7 tautomer.